Cross‐national epidemiology of panic disorder and panic attacks in the world mental health surveys (2016)
Context The scarcity of cross‐national reports and the changes in Diagnostic and Statistical Manual version 5 (DSM‐5) regarding panic disorder (PD) and panic attacks (PAs) call for new epidemiological data on PD and PAs and its subtypes in the general population. Objective To present representative data about the cross‐national epidemiology of PD and PAs in accordance with DSM‐5 definitions. Design and setting Nationally representative cross‐sectional surveys using the World Health Organization Composite International Diagnostic Interview version 3.0. Participants Respondents (n = 142,949) from 25 high, middle, and lower‐middle income countries across the world aged 18 years or older. Main outcome measures PD and presence of single and recurrent PAs. Results Lifetime prevalence of PAs was 13.2% (SE 0.1%). Among persons that ever had a PA, the majority had recurrent PAs (66.5%; SE 0.5%), while only 12.8% fulfilled DSM‐5 criteria for PD. Recurrent PAs were associated with a subsequent onset of a variety of mental disorders (OR 2.0; 95% CI 1.8–2.2) and their course (OR 1.3; 95% CI 1.2–2.4) whereas single PAs were not (OR 1.1; 95% CI 0.9–1.3 and OR 0.7; 95% CI 0.6–0.8). Cross‐national lifetime prevalence estimates were 1.7% (SE 0.0%) for PD with a median age of onset of 32 (IQR 20–47). Some 80.4% of persons with lifetime PD had a lifetime comorbid mental disorder. Conclusions We extended previous epidemiological data to a cross‐national context. The presence of recurrent PAs in particular is associated with subsequent onset and course of mental disorders beyond agoraphobia and PD, and might serve as a generic risk marker for psychopathology.